Viewing angle control and fast switching of a hybrid-aligned liquid crystal cell using a vertical bias field. Issue 1 (2nd January 2016) - Park, Young-Jin; Choi, Tae-Hoon; Kim, Jung-Wook; Yoon, Tae-Hoon
Abstract : Proposed herein is a method of controlling the viewing angle in a hybrid-aligned liquid crystal (LC) cell using a vertical bias electric field. Using the proposed method, the viewing angle can be continuously controlled by changing the bias voltage. A vertical bias electric field is applied to the cell for a wide viewing angle whereas no bias electric field is applied for a narrow viewing angle. The proposed cell shows a submillisecond response time.